Influence of axial heat conduction in solid walls and fins on the overall thermal performance of an additively manufactured high-temperature heat exchanger. (25th July 2022) - Fuchs, Marco; Luo, Xing; Kabelac, Stephan
Highlights: 1D-model to calculate axial heat conduction in walls and fins of a plate-fin heat exchanger. Experimental testing of the additive manufactured high-temperature heat exchanger. Model can predict the effectiveness within 1–6% compared to exp. results. Axial heat conduction reduces the effectiveness by up to5.5% NTU-value is reduced by up to 50% at balanced flow. Abstract: Due to the increasing use of high-temperature processes in mobile applications, the demand for compact and efficient high-temperature heat exchangers continues to rise. However, with increasingly reduced installation space, the parasitic effect of axial heat conduction in the wall material of the heat exchanger is also gaining considerable influence. In this manuscript, the influence of axial heat conduction in the wall and fin material on the thermal performance of an additively manufactured high temperature heat exchanger is to be examined. For this purpose, an analytical calculation model as well as the analytical solution method is presented and successfully validated by means of experimentally recorded measurement data of an additively manufactured heat exchanger, which was tested at temperatures up to 750 °C. Subsequently, the calculation programme is used to determine the influence of the axial heat conduction on the effectiveness as well as on the NTU value of an additively manufactured Plate-Fin heat exchanger. The results show a drop in the NTU value of up to 50% at balanced flow compared to the case without heat conduction, which reduces the effectiveness and thus the performance of the heat exchanger by up to 5.5%.